Synthesized and Characterization of Gold and Silver Nanoparticles and Use as Catalyst for Preparation of 4-Aminophenol - Ho Lee, Jeong; Kyu Hong, Sung; Bae Ko, Weon (Asian Journal of Chemistry, 2011)
This paper reports the synthesis and characterization of metal (Au, Ag) nanoparticle catalysts supported on a carbon nanomaterial for the preparation of 4-aminophenol. Gold and silver nanoparticles were deposited on individually the surface of carbon nanocolloids in an aqueous solution. 4-Aminophenol was synthesized in an aqueous solution containing gold and silver nanoparticles embedded in the carbon nanocolloids and examined by UV-VIS spectroscopy. The catalytic activity was observed as a function of time. The fabricated carbon nanocolloids coated with gold and silver nanoparticles showed superior catalytic performance toward the preparation of 4-aminophenol than the corresponding gold and silver nanoparticles, respectively. The carbon nanocolloids acted as a support for the homogeneous dispersion of gold and silver nanoparticles in an aqueous solution. The nature of the resulting the carbon nanocolloids coated with gold and silver nanoparticles was examined by X-ray diffraction and transmission electron microscopy.